The release of Negro Huasteco 81, a new Mexican bean variety tolerant to golden mosaic virus - Yoshii, K.; Rodríguez Rodríguez, José Raúl (1983)
The development and release of Negro Huasteco 81, a black- seeded bush bean var., are described. This line was consistently the most tolerant from a total of 25 BGMV-tolerant lines and var. introduced from a collaborative project between CIAT and the Instituto de Ciencia y Tecnologia Agricolas, Guatemala. Trials were carried out in the state of Veracruz in 1980 and throughout the tropics of Mexico in 1981. Negro Huasteco 81 is a selection from the cross of ICA-Pijao x Porrillo 70; it also shows reasonably wide adaptation and resistance to BCMV, rust, and angular leaf spot. (CIAT)